Fractional exhaled nitric oxide in the assessment of exercise-induced bronchoconstriction: A multicenter retrospective analysis of UK-based athletes - Dickinson, J.; Gowers, W.; Sturridge, S.; Williams, N.; Kippelen, P.; Simpson, A.; Jackson, A.; Hull, J. H.; Price, O. J. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Introduction Exercise-induced bronchoconstriction (EIB) is not only highly prevalent in people with asthma, but can also occur independently, particularly in athletes. Fractional exhaled nitric oxide (FeNO) is an indirect biomarker of type 2 airway inflammation that has an established role in the assessment and management of asthma. The aim was to evaluate the value of FeNO in the assessment of EIB in athletes.